Preliminary data on lansnails (Gastropoda) in Xom Du village, Xuan Son national park, Phu Tho province - Khac, Hoang Ngoc; Khac, Hoang Ngoc; Anh, Khong Thuy (Academia Journal of Biology, 2012)
By research results on landsnails in Xom Du village, Xuan Son national park, Phu Tho province in 2008-2009, 44 species and subspecies belonging to two subclasses Prosobranchia and Pulmonata has been recorded. In this species composition, there are 36 of species of Pulmonata (81.8%) in 11 families (Trochomorphidae, Ariophantidae, Camaenidae, Clausiliidae, Helicarionidae, Helicidae, Streptaxidae, Subulinidae, Zonnitidae and Pupillidae); and 8 species of Prosobranchia (18.2%) in 3 families (Cyclophoridae, Diplommatinidae and Pupinidae). Almost species are living in jungle forests on limestone mountains and a few in other biotopes. Among them Ariophantidae is the most abundant family, with genus Macrochlamys 7 species.